PENEGAKAN SANKSI DAN ASAS KEWARGANEGARAAN DALAM KASUS PEMBERIAN OBAT KERAS TANPA RESEP DOKTER DI APOTEK - Linda Nur Rahmawati; Haqi, Moch Alif; Lubna Khairunisa; Miftah Fajar Raihan Firmansyah; Sugiartiningsih (Ganesha Civic Education Journal, 2026)
The misuse of prescription-only drugs, particularly antibiotics, has become a critical public health issue in Indonesia, driving antimicrobial resistance (AMR) which caused 147,000 deaths in 2021 and an annual economic loss of IDR 2.4 trillion. Despite regulations, illegal access remains as high as 41% in licensed pharmacies. This study examines prescription drug regulations, the role of pharmacists, and legal sanctions, while integrating professional integrity with national defense (Bela Negara) values. Using a normative analytical literature review of primary sources (Health Law No. 17/2023, PMK No. 73/2016, BPOM regulations) and secondary data, the results indicate a dominance of non-prescription amoxicillin sales driven by low pharmacist knowledge and weak field oversight, rendering current regulations ineffective. This is exacerbated by poor public education and the lack of reliable prescription verification. In conclusion, a digital transformation for real-time prescription validation is required, alongside strengthened pharmaceutical care standards (assessment, counseling, and MTM). These measures must be supported by consistent criminal sanctions and civic-based education (PKn) to bolster practitioner integrity, break the chain of AMR, and ensure rational drug use.